TYPES OF PEDAGOGICAL TECHNOLOGY AND LESSON MODULES - Mamasoatov , Dilshod Ravshanovich (Educational Research in Universal Sciences, 2023)
In this article, the main laws of the science of educational technologies are explained philosophically. In addition, the specific laws of education and training technologies in Western countries are revealed. In particular, the main periods of development of educational technology were analyzed. Also, current methods of educational technologies at different levels are interpreted from a scientific point of view.